THE EFFECT OF ACADEMIC STRESS ON STUDENTS’ MENTAL HEALTH IN HIGHER EDUCATION - Vera Sriwahyuningsih; Mufadhal Barseli (Media Inovasi Pendidikan dan Publikasi, 2026)
Academic stress is a psychological condition experienced by university students due to high academic demands, excessive workload, competitive academic environments, poor time management, and limited social support. These conditions potentially affect students’ mental health in higher education settings. This study aims to analyze the effect of academic stress on students’ mental health. The research employed a quantitative approach with a correlational design. The sample consisted of 150 active university students selected using purposive sampling technique. Data were analyzed using simple linear regression. The results revealed a significant negative correlation between academic stress and students’ mental health (r = -0.562; p < 0.001). The coefficient of determination (R²) was 0.316, indicating that academic stress contributed 31.6% to the variance in students’ mental health, while the remaining 68.4% was influenced by other factors outside this study. These findings suggest that higher levels of academic stress are associated with lower levels of mental health. Therefore, preventive interventions through guidance and counseling services, adaptive coping training, and strengthened social support systems are essential in higher education institutions.